Lead‐ and Iodide‐Deficient (CH3NH3)PbI3 (d‐MAPI): The Bridge between 2D and 3D Hybrid Perovskites. (15th November 2017) - Leblanc, Antonin; Mercier, Nicolas; Allain, Magali; Dittmer, Jens; Fernandez, Vincent; Pauporté, Thierry
Abstract: 3D and 2D hybrid perovskites, which have been known for more than 20 years, have emerged recently as promising materials for optoelectronic applications, particularly the 3D compound (CH3 NH3 )PbI3 (MAPI). The discovery of a new family of hybrid perovskites called d ‐MAPI is reported: the association of PbI2 with both methyl ammonium (MA + ) and hydroxyethyl ammonium (HEA + ) cations leads to a series of five compounds with general formulation (MA)1−2.48x (HEA)3.48x [Pb1−x I3−x ]. These materials, which are lead‐ and iodide‐deficient compared to MAPI while retaining 3D architecture, can be considered as a bridge between the 2D and 3D materials. Moreover, they can be prepared as crystallized thin films by spin‐coating. These new 3D materials appear very promising for optoelectronic applications, not only because of their reduced lead content, but also in account of the large flexibility of their chemical composition through potential substitutions of MA +, HEA +, Pb 2+ and I − ions.